(untitled) (Business Vision, 2025)
In the ecuadorian context, public policies for the development of entrepreneurship in the Popular and Solidarity Economy represent a crucial challenge. In this scenario, the Popular and Solidarity Economy plays a fundamental role by redistributing the surplus in favor of producers and by consolidating small businesses to achieve economies of scale and promote association and cooperation. To analyze this situation, a methodology with a cross-sectional qualitative and quantitative approach was used. The methodological design included a historical-conceptual analysis, complemented by a bibliometric and systematic analysis. This approach allowed us to collect information on public policies, their evolution and their impact on entrepreneurship within the Popular and Solidarity Economy. Among the main results, strengths stand out such as the favorable legal and institutional framework and the support programs of the Ecuadorian government towards entrepreneurs. However, weaknesses are also identified, such as the lack of articulation between the different institutions, the scarce entrepreneurial culture and the lack of specialized financing. In conclusion, although public policies offer an alternative for the most disadvantaged sectors through inclusive support in constitutions and legislation, it is anticipated that many ventures will not survive in the long term.